(untitled) (Global Journal of Medical Research, 2020)
Hypohidrotic Ectodermal Dysplasia (HED) is part of a heterogeneous group of inherited diseases that affect the structures derived from the ectodermal tissue. Among the common oral manifestations, hypodontia is observed, generating the need for prosthetic rehabilitation. The objective of this paper is to present the main difficulties in the oral rehabilitation of patients with HED in the age group 0 from to 16 years old. A bibliographic search was done using articles published between 2004 and 2019 in the Pubmed database, using the MeSH terms Hypohidrotic Ectodermal Dysplasia AND Dental Rehabilitation. There were 26 articles available for download, reporting a total of 46 patients. The main limiting factors found in these patients are: hyposalivation, atrophic alveolar ridge, decreased vertical dimension of occlusion and varying levels of hypodontia. The constant bone growth of child and adolescent patients also limits the prosthetic rehabilitation options and decreases the fit index of the confectioned prostheses. In addition, psychological and social factors should be considered, as it is necessary to promote a treatment in which the young patient is able to adapt and maintain it.